Policy mixes to achieve sustainable mobility after the COVID-19 crisis. (June 2021) - Griffiths, S.; Furszyfer Del Rio, D.; Sovacool, B.
Abstract: The COVID-19 pandemic has the potential to have lasting impacts on energy and the environment at the global scale. Shelter-in-place measures implemented to mitigate the spread of COVID-19 have resulted in expectations for 2020 global energy demand to contract by nearly 5% with related global CO2 emissions declining by as much as 7%. Exactly how long and to what extent we will see continue to see energy demand, CO2 and related greenhouse gas (GHG) emission destruction resulting from COVID-19 is uncertain but dependent on global policy responses to the pandemic. Policy responses targeting the transportation sector, particularly ground-based transportation, can stimulate a sustainable mobility transition that mitigates the potential for long-term environmental damage. This paper reviews and examines social and cultural dynamics of transportation and extends state-of-the-art knowledge to consider how events surrounding the COVID-19 crisis may have created a sustainable mobility opportunity though (1) avoiding unnecessary transportation volume, (2) shifting transportation norms and practices and/or (3) improving the carbon-efficiency of transportation systems. Relevant policies for a low-carbon transportation transition are considered and those most appropriate to the current context are proposed with consideration of key factors that may help or hinder their implementation success. Highlights: Shows how Covid-19 creates an opportunity for sustainable mobility. Defines three narratives to assess the sustainable mobility opportunity. Describes avoid, shift and improve policies for sustainable mobility. Shows that policy mixes need to prioritize cities and consider local context. Suggests policies must promote and protect zero carbon and public mobility.